Financial Literacy at an Early Age: The Role of Digital Technology in Students' Financial Literacy - Muniarty, Puji; Rimawan, M; Ovriyadin, Ovriyadin; Wulandari, Wulandari; Dwiriansyah, M Syukur (Universitas Negeri Gorontalo, 2025)
Purpose: This research aims to explore the extent to which the role of digital technology can increase financial literacy among students. The problems in the study are the low financial literacy of students and not optimal use of smartphones and the internet, digital technology as an effective solution in applying financial principles interactively easily accessible, not all students have the same access to financial technology and the lack of specific research that discusses the effectiveness of digital technology in increasing financial understanding among students.Design/Methodology/Approach: The population in this study was all students in semesters IV (Four) and VI (Six) of the Financial Management concentration study program at the Sekolah Tinggi Ilmu Ekonomi Bima, with a total sample of 161 students, and the sampling used was purposive.Findings: The research results show that the use of digital technology plays an important role in increasing financial literacy among students. Digital financial applications, social media, and online education platforms are proven to be able to help students manage personal finances, understand basic financial concepts, and make wiser financial decisions. Apart from that, financial literacy in the digital era needs to continue to be improved through the integration of technology-based financial education in the curriculum and the provision of digital platforms that are trusted and easy for students to access. It is believed that this approach can create a younger generation that is more financially intelligent and ready to face future economic challenges.